Calvinisme dan Ilmu Pengetahuan: Suatu Tinjauan Filosofis terhadap Pemikiran Abraham Kuyper - Antonius Steven Un (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: This article is focused on systematic explanation of Abraham Kuypers thought on Calvinism and science. Some of significant contributions of Calvinism are the theological foundation of science and its liberation from churchs invasion. This article uses a philosophical approach in its methodology and not a theological one. Therefore, Ifrequently make critical dialogues with the philosophy of science in reading and analyzing Kuypers notion. Final ending of this research is an articulation of its implications to the ethics of science. On this point, I will consider the contribution of David Resnick. KEYWORDS: Calvinism, science, Abraham Kuyper, ethics.